SIMULATION OF THE INFLUENCE OF ELECTRODE TIP ANGLE ON THE ARC VOLTAGE DIFFERENCE OF GAS TUNGSTEN ARC WELDING (GTAW) PROCESS - Pham Nhat Phuong; Vo Tuyen; Dinh Le Cao Ky; Dang Van Hai; Trinh Tien Tho (HUIT Journal of Science, 2025)
Gas tungsten arc welding (GTAW) is a versatile all-position process that can be used to weld metals and a variety of metals. In this paper, a simulation method was used to determine the effect of the non-consumable tungsten electrode tip taper angle on the arc voltage difference. Simulation results have shown that (1) The arc voltage difference increases rapidly as the electrode tip angle increases in the range from 9 degree to 30 degree for different welding currents; (2) The arc voltage difference reaches its maximum value at an angle of 150 degree for welding current I = 100 A, reaching its maximum value at an angle of 60 degree for welding currents I = 200 A and I = 250A ; (3) The arc voltage difference increases with the increase of arc length and welding current; (4) When the electrode tip angle increases between 9 degree and 60 degree, the arc voltage increases with the electrode tip angle; Above 60 degree, it depends on the arc temperature and thus the arc voltage increases or decreases.